Program assessment on the Ecological Social Waste Management Act of 2000 in Brgy. 37, Reclamation Area, Tacloban City. - Alvero, John Martin P.; Isaga, Marjune S. (Tacloban City John Martin Alvero, 2012)
This paper depicts the waste management practices of households and the extent of the compliance to the Republic Act 9003, otherwise known as The Ecological Solid Waste Management Act of 2000, in the barangay level. The study was conducted in Barangay 37, Reclamation Area, Tacloban City.
The research findings showed that households have difficulty in segregating their wastes and garbage. The households solely relies their wastes disposal on the city's garbage collection. Recycling is practiced only on some specific wastes because of market opportunities. This paper points out the noncompliance of Sangguniang Barangay of Barangay 37 to the implementing rules and regulations of the RA 9003. Mainly, lack of information (on the part of the respondents), lack of coordination and cooperation between the Barangay officials and the people, and difficulty in acquiring available land for material recovery use are among the reasons that influence the non-compliance.
This paper furtherly suggests that community-scale dissemination on the appropriate information and more effective and more efficient solid waste management should be primarily advocated in order to promote community awareness. The Sangguniang Barangay should formulate a long-term and inclusive solid waste management programs that would persuade community cooperation and participation.
Undergraduate thesis (B.A.S.S. Economics)--University of the Philippines, Tacloban
Keywords: Social Science